Budding trends in integrated pest management using advanced micro- and nano-materials: challenges and perspectives - Khandelwal, Neha; Barbole, Ranjit S.; Banerjee, Shashwat S.; Chate, Govind P.; Biradar, Ankush V.; Khandare, Jayant J.; Giri, Ashok P. (Journal of Environmental Management, 2016)
One of the most vital supports to sustain human life on the planet earth is the agriculture system that has been constantly challenged in terms of yield. Crop losses due to insect pest attack even after excessive use of chemical pesticides, are major concerns for humanity and environment protection. By the virtue of unique properties possessed by micro and nano-structures, their implementation in Agri-biotechnology is largely anticipated. Hence, traditional pest management strategies are now forestalling the potential of micro and nanotechnology as an effective and viable approach to alleviate problems pertaining to pest control. These technological innovations hold promise to contribute enhanced productivity by providing novel agrochemical agents and delivery systems. Application of these systems engages to achieve: i) control release of agrochemicals, ii) site-targeted delivery of active ingredients to manage specific pests, iii) reduced pesticide use, iv) detection of chemical residues, v) pesticide degradation, vi) nucleic acid delivery and vii) to mitigate post-harvest damage. Applications of micro and nano-technology are still marginal owing to the perception of low economic returns, stringent regulatory issues involving safety assessment and public awareness over their uses. In this review, we highlight the potential application of micro and nano-materials with a major focus on effective pest management strategies including safe handling of pesticides. (C) 2016 Elsevier Ltd. All rights reserved.

RNAi of selected candidate genes interrupts growth and development of Helicoverpa armigera - Chikate, Yojana R.; Dawkar, Vishal V.; Barbole, Ranjit S.; Tilak, Priyadarshini V.; Gupta, Vidya S.; Giri, Ashok P. (Pesticide Biochemistry and Physiology, 2016)
Helicoverpa armigera is one of the major crop pests and is less amenable to current pest control approaches. RNA interference (RNAi) is emerging as a potent arsenal for the insect pest control over current methods. Here, we examined the effect on growth and development in H. armigera by targeting various enzymes/proteins such as proteases like trypsins (HaTry2, 3, 4 and 6), chymotrypsin (HaChy4) and cysteine protease like cathepsin (HaCATHL); glutathione S-transferases (HaGST1a, 6 and 8); esterases (HaAce4, HaJHE); catalase (HaCAT); super-oxide-dismutase (HaCu/ZnSOD); fatty acid binding protein (HaFabp) and chitin deacetylase (HaCda5b) through dsRNA approach. Significant downregulation of cognate mRNA expression and reduced activity of trypsin and GST-like enzyme were evident upon feeding candidate dsRNAs to the larvae. Among these, the highest mortality was observed in HaAce4 dsRNA fed larvae followed by HaJHE; HaCAT; HaCuZnSOD; HaFabp and HaTry3 whereas remaining ones showed relatively lower mortality. Furthermore, the dsRNA fed larvae showed significant reduction in the larval mass and abnormalities at the different stages of H. armigera development compared to their control diets. For example, malformed larvae, pupae and moth at a dose of 60 pg/day were evident in high number of individual insects fed on dsRNA containing diets. Moreover, the growth and development of insects and moths were retarded in dsRNA fed larvae. These findings might provide potential new candidates for designing effective dsRNA as pesticide in crop protection. (C) 2016 Elsevier Inc. All rights reserved.

Improved tolerance against helicoverpa armigera in transgenic tomato over-expressing multi-domain proteinase inhibitor gene from capsicum annuum - Tanpure, Rahul S.; Barbole, Ranjit S.; Dawkar, Vishal V.; Waichal, Yashashree A.; Joshi, Rakesh S.; Giri, Ashok P.; Gupta, Vidya S. (Physiology and Molecular Biology of Plants, 2017)
Plant proteinase inhibitors (PIs) are plant defense proteins and considered as potential candidates for engineering plant resistances against herbivores. Capsicum annuum proteinase inhibitor (CanPI7) is a multi-domain potato type II inhibitor (Pin-II) containing four inhibitory repeat domains (IRD), which target major classes of digestive enzymes in the gut of Helicoverpa armigera larvae. Stable integration and expression of the transgene in T1 transgenic generation, were confirmed by established molecular techniques. Protein extract of transgenic tomato lines showed increased inhibitory activity against H. armigera gut proteinases, supporting those domains of CanPI7 protein to be effective and active. When T1 generation plants were analyzed, they exhibited antibiosis effect against first instar larvae of H. armigera. Further, larvae fed on transgenic tomato leaves showed delayed growth relative to larvae fed on control plants, but did not change mortality rates significantly. Thus, better crop protection can be achieved in transgenic tomato by overexpression of multi-domain proteinase inhibitor CanPI7 gene against H. armigera larvae.

Azadirachtin-A from azadirachta indica impacts multiple biological targets in cotton bollworm helicoverpa armigera - Dawkar, Vishal V.; Barage, Sagar H.; Barbole, Ranjit S.; Fatangare, Amol; Grimalt, Susana; Haldar, Saikat; Heckel, David G.; Gupta, Vidya S.; Thulasiram, Hirekodathakallu V.; Svatos, Ales.; Giri, Ashok P. (ACS Omega, 2019)
Azadirachtin-A (AzaA) from the Indian neem tree (Azadirachta indica) has insecticidal properties; however, its molecular mechanism remains elusive. The ``targeted and nontargeted proteomic profiling'', metabolomics, matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) imaging, gene expression, and in silico analysis provided clues about its action on Helicoverpa armigera. Fourth instar H. armigera larvae fed on AzaA-based diet (AzaD) suffered from significant mortality, growth retardation, reduced larval mass, complications in molting, and prolonged development. Furthermore, death of AzaD-fed larvae was observed with various phenotypes like bursting, blackening, and half-molting. Liquid chromatography-mass spectrometry (LC-MS) data showed limited catabolic processing of ingested AzaA and dramatic alternations of primary metabolism in H. armigera. MALDI-TOF imaging indicated the presence of AzaA in midgut of H. armigera. In the gut, out of 79 proteins identified, 34 were upregulated, which were related to digestion, immunity, energy production, and apoptosis mechanism. On the other hand, 45 proteins were downregulated, including those from carbohydrate metabolism, lipid metabolism, and energy transfer. In the hemolymph, 21 upregulated proteins were reported to be involved in immunity, RNA processing, and mRNA-directed protein synthesis, while 7 downregulated proteins were implicated in energy transfer, hydrolysis, lipid metabolism, defense mechanisms, and amino acid storage-related functions. Subsequently, six target proteins were identified using labeled AzaA that interacted with whole insect proteins. In silico analysis suggests that AzaA could be efficiently accommodated in the hydrophobic pocket of juvenile hormone esterase and showed strong interaction with active site residues, indicating plausible targets of AzaA in H. armigera. Quantitative polymerase chain reaction analysis suggested differential gene expression patterns and partly corroborated the proteomic results. Overall, data suggest that AzaA generally targets more than one protein in H. armigera and hence could be a potent biopesticide.

Identification and characterization of the key enzyme in the biosynthesis of the neurotoxin beta-ODAP in grass pea - Goldsmith, Moshe; Barad, Shiri; Knafo, Maor; Savidor, Alon; Ben-Dor, Shifra; Brandis, Alexander; Mehlman, Tevie; Peleg, Yoav; Albeck, Shira; Dym, Orly; Ben-Zeev, Efrat; Barbole, Ranjit S.; et al. (Journal of Biological Chemistry, 2022)
Grass pea (Lathyrus sativus L.) is a grain legume commonly grown in Asia and Africa for food and forage. It is a highly nutritious and robust crop, capable of surviving both droughts and floods. However, it produces a neurotoxic compound, beta-N- oxalyl-L-alpha,beta-diaminopropionic acid (beta-ODAP), which can cause a severe neurological disorder when consumed as a primary diet component. While the catalytic activity associated with beta-ODAP formation was demonstrated more than 50 years ago, the enzyme responsible for this activity has not been identified. Here, we report on the identity, activity, 3D structure, and phylogenesis of this enzyme-beta-ODAP synthase (BOS). We show that BOS belongs to the benzylalcohol O-acetyltransfer-ase, anthocyanin O-hydroxycinnamoyltransferase, anthranilate N-hydroxycinnamoyl/benzoyltransferase, deacetylvindoline 4-O-acetyltransferase superfamily of acyltransferases and is structurally similar to hydroxycinnamoyl transferase. Using molecular docking, we propose a mechanism for its catalytic activity, and using heterologous expression in tobacco leaves (Nicotiana benthamiana), we demonstrate that expression of BOS in the presence of its substrates is sufficient for beta-ODAP production in vivo. The identification of BOS may pave the way toward engineering beta-ODAP-free grass pea cultivars, which are safe for human and animal consumption.

Article chitinase inhibition induces transcriptional dysregulation altering ecdysteroid-mediated control of spodoptera frugiperda development - Barbole, Ranjit S.; Sharma, Shivani; Patil, Yogita; Giri, Ashok P.; Joshi, Rakesh S. (Iscience, 2024)
Chitinases and ecdysteroid hormones are vital for insect development. Crosstalk between chitin and ecdysteroid metabolism regulation is enigmatic. Here, we examined chitinase inhibition effect on Spodopsilencing and overexpression resulted in ecdysone receptor deregulation. Transcription factors, like Neverland, and other ecdysteroid biosynthesis genes might lead to their upregulation in berberine-fed chitinase activity's impact on ecdysone biosynthesis and its transcriptional crosstalk.

Engineering inhibitory repeat domains of Pin-II type proteinase inhibitors indicate their high structural-functional tolerance to mutagenesis - Barbole, Ranjit S.; Joshi, Rakesh S.; Giri, Ashok P. (Biochemical and Biophysical Research Communications, 2024)
Plant proteinase inhibitors (PIs) are critical in defending against biotic stress. Most PIs contain an inhibitory repeat domain (IRD), which serves as the functional component, displaying a high degree of sequence and structural conservation. In this study, we examined the structural and functional resilience of IRDs using a combination of computational modeling and experimental validation. We have taken an evolution-based approach to enhance the PIs effectiveness of two previously identified Capsicum annuum IRDs, IRD4 and IRD10. Through in silico site-saturation mutagenesis of IRD4 and IRD10, we identified key sites associated with enhanced PI activity for targeted mutagenesis. Binding energy predictions for a mutant IRD library, tested against target proteases, suggested that positions R11 and N32 in IRD4 and N32 and H33 in IRD10 were promising candidates for further modification to improve inhibitory potential. Subsequent experimental validation revealed that the mutant proteins IRD4_R11K and IRD4_N32S exhibited stronger chymotrypsin inhibition than the wild-type (WT) IRD4. Similarly, the mutants IRD10_N32S and IRD10_H33 N demonstrated improved trypsin inhibition relative to the WT IRD10. These findings indicate that engineered IRD variants can tolerate structural changes while maintaining or enhancing their inhibitory activity against target proteases. Overall, this study demonstrates the potential of engineering PIs to increase their structural and functional resilience, offering new opportunities for biotechnological applications.
Keywords: Capsicum annum; Inhibitory repeat domain; molecular modeling; plant proteinase inhibitors; Proteases; Saturation mutagenesis

LsBOS utilizes oxalyl-CoA produced by LsAAE3 to synthesize β-ODAP in grass pea - Goldsmith, Moshe; Avram, Liat; Brandis, Alexander; Mehlman, Tevie; Ben-Dor, Shifra; Peleg, Yoav; Ben-Zeev, Efrat; Barbole, Ranjit S.; Reich, Ziv (Nature Communications, 2024)